To complete the input-output table for the function \( f(x) = - (x + 1)^2 + 4 \), we can calculate the values of \( f(x) \) for each of the given \( x \) values:
-
For \( x = -1 \): \[ f(-1) = -((-1) + 1)^2 + 4 = -0^2 + 4 = 4 \]
-
For \( x = 0 \): \[ f(0) = -(0 + 1)^2 + 4 = -1^2 + 4 = -1 + 4 = 3 \]
-
For \( x = 1 \): \[ f(1) = -(1 + 1)^2 + 4 = -2^2 + 4 = -4 + 4 = 0 \]
-
For \( x = 2 \): \[ f(2) = -(2 + 1)^2 + 4 = -3^2 + 4 = -9 + 4 = -5 \]
Now, we summarize the values:
- \( f(-1) = 4 \)
- \( f(0) = 3 \)
- \( f(1) = 0 \)
- \( f(2) = -5 \)
Based on these calculated outputs, the largest output occurs at \( x = -1 \), where \( f(-1) = 4 \).
So the answer is: x = -1